Parenting adolescents: Parent-Teen communication training - Efi Fitriana; Syipa Husni Fadillah; Fitri Ariyanti Abidin (University of Merdeka Malang, 2023)
Puberty is often experienced by adolescents in relation to psychological changes, including letting go of dependence on parents to achieve greater independence. Adolescents begin to spend more time with their friends, and share less information with their parents. However, support and direction from parents are still needed by adolescents, considering that they will grow into adults with all the complexity of their problems. So parents need to understand the changes that adolescents are experiencing, and how to assist adolescents in dealing with these changes.